PENGARUH OLEORESIN DAUN JERUK PURUT (Citrus hystrix DC.) PADA EDIBLE COATING TERHADAP KUALITAS SOSIS SAPI BEKU (Jurnal Teknologi Industri Pertanian, 2016)
Sausages is a nutritious and perishable food so that it needs treatment to extent the shelf life. The aim ofthis research was to find out the effect of kaffir lime leave oleoresin on beef sausage quality such asmicrobiological and physicochemical characteristic during frozen storage (-10±2°C). The completelyRandomized Design (CRD) was used with one factor was the concentration of kaffir lime leave oleoresin inedible packaging at 0%, 0.05%, and 0.15%.. The observations were done more 0, 1, 2, 3, and 4 months. Theresults showed that the addition of kaffir lime leave oleoresin on edible packaging affect the beef sausagequality. With lower amount of microbes and more stabilize color of beef sausage. The increase of kaffir limeleave oleoresin decreased TVB and pH value of beef sausage.Keywords: beef sausage, Citrus hystrix, edible packaging, oleoresin